Quantifying the burden of cardiovascular diseases among people living with HIV in sub-Saharan Africa: findings from a modeling study for Uganda. (2020) - Kintu, Alexander; Sando, David; Guwatudde, David; Bahendeka, Silver; Kawungezi, Peter C; Mutungi, Gerald; Muyindike, Winnie; Menzies, Nicolas; Okello, Samson; Danaei, Goodarz; Verguet, Stéphane
No abstract available